A comparative study on the effects of rewarming interventions plastic sheath and stockinet on preterms' body temperature - De Ocampo, Rachelle O.; Guerra, Allan G.; Montezon, Catherine U.; Mostajo, Marivic B.; Pacis, Irene Joyce S.; Sablay, Ma. Rufina Michelle P.
This is a comparative study on the effects of 2 rewarming interventions: plastic shealth and stockinet on preterm’s body temperature. The objectives of the study included: 1) To compare the temperature of preterm infants after the application of two rewarming interventions at 0-minute pretest, 15-, 30-, 45-, 60-, and 75-minute posttests 2) To determine if the study variables (age of gestation, present age and present weight) are associated with the preterm’s response to the intervention. This study utilized the repeated measures quasi-experimental design. Case finding and data collection were conducted at the Neonatal Intensive Care Unit, particularly NICU 2 of UP-PGH. A total of 20 subjects were included in the study.Each was randomly assigned to only one intervention (10 for stockinet and 10 for plastic sheath). Upon application of the assigned intervention, temperature readings were repeatedly taken at 15, 30, 45, 60 and 75 minutes. The statistical methods for data analysis included Pearson’s Product-Moment Correlation, Pooled T-test and Repeated Measures ANOVA. Findings showed that 1) There is no significant difference between the temperatures of the stockinet and plastic sheath group. 2) There is a significant difference among the temperatures at times 45, 60 and 75 minutes. 3) There is no significant interaction between rewarming intervention and the six-time period. Findings also showed that there is no significant relationship between the study variables (age of gestation, present age and present weight) and the preterm’s response to the intervention. Based on these facts, the researchers recommend the use of stockinet as an alternative rewarming intervention to plastic sheath.